Katherine . The Ballad of Andy Crocker - Spacek, Sissy; Winkler, Henry; Majors, Lee.; Heatherton, Joey. ([United States] Dollar Entertainment, 2004)
Katherine/The Ballad of Andy Crocker are two classic drama movies and was released Feb 22, 2005 by the Mill Creek Entertainment studio.
Durations: 97 min., 90 min.
Katherine: Sissy Spacek, Henry Winkler, Art Carney. The Ballad of Andy Crocker: Lee Majors, Joey Heatherton, Jimmy Dean.
In English.
Keywords: Social change -- Drama; Drama